Remediation of oil-contaminated artic wetland using electrooxidation combined with permeable reactive barrier - Eriksson, Mattis (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2024)
Oil spills can cause significant damage to living organisms and the environment. Oil spills have historically had devastating consequences for the environment and wildlife. Both the oil itself and its by-products such as polycyclic aromatic hydrocarbons are harmful for living organisms and wildlife. This work investigated the possibility of cleaning oil pollution in an arctic wetland using electrokinetic remediation in combination with a permeable reactive barrier. Three experimental setups were compared to evaluate the degree of remediation. One cell contained only oil-contaminated soil and was used a control, one cell contained contaminated soil and a reactive barrier filled with thermally treated peat granulate (FloatAbsorb) and the third cell was filled the contaminated soil, the barrier and was complemented with electrodes inserted directly into the soil and the barrier for electrooxidation. Deionized water was pumped through the cells to simulate the natural groundwater flow. The percolated water was collected over nine weeks and analyzed every two weeks for aliphatic and aromatic compounds, PAH and oil index. The soil was analyzed before the experiment started and in all three cells after the experiment for aliphatic and aromatic compounds, PAH and oil index. The water analysis showed that most analytes were below detectable levels throughout the entire study period. pyrene and some aliphatic compounds could be detected. The soil analysis after the experiment showed that none of the analyzed aromatic compounds could have been detected in any of the three cells. For both aliphatic fraction >C12-16 and >C16-35, the highest concentration was found in cell with soil and reactive barrier and the lowest concentration in cell with electrooxidation treatment. The concentration in fraction >C12-C16 varied between 494 mg/kg and 578 mg/kg, and in fraction >C16-C35 between 3890 mg/kg to 4620 mg/kg. Concerning the total concentration of oil in the fraction >C10-C40, the highest concentrations were in ...